A Shamanic Pneumatology in a Mystical Age of Sacred Sustainability: The Spirit of the Sacred Earth - Fung, Jojo M (Archīum Ateneo, 2017)
This book represents a germinal effort that urges all religious and world leaders to savor the mystical spirituality, especially the cosmology and spirituality of sacred sustainability of the indigenous peoples. The power of indigenous spirit world is harnessed for the common good of the indigenous communities and the regenerative power of mother earth. This everyday mysticism of the world as spirited and sacred serves to re-enchant a world disillusioned by the unsustainability of destructive economic systems that have spawned the current ecological crises. Author Jojo Fung offers insight from his lived-experience and this book represents his effort to correlate the indigenous spirit world with Catholic Pneumatology and articulate the activity of God’s Spirit as the Spirit of Sacred Sustainability.